Embedded Systems Design The ARTIST Roadmap for Research and Development - Bouyssounouse, Bruno; Sifakis, Joseph; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Embedded systems now include a very large proportion of the advanced products designed in the world, spanning transport (avionics, space, automotive, trains), electrical and electronic appliances (cameras, toys, televisions, home appliances, audio systems, and cellular phones), process control (energy production and distribution, factory automation and optimization), telecommunications (satellites, mobile phones and telecom networks), and security (e-commerce, smart cards), etc. The extensive and increasing use of embedded systems and their integration in everyday products marks a significant evolution in information science and technology. We expect that within a short timeframe embedded systems will be a part of nearly all equipment designed or manufactured in Europe, the USA, and Asia. There is now a strategic shift in emphasis for embedded systems designers: from simply achieving feasibility, to achieving optimality. Optimal design of embedded systems means targeting a given market segment at the lowest cost and delivery time possible. Optimality implies seamless integration with the physical and electronic environment while respecting real-world constraints such as hard deadlines, reliability, availability, robustness, power consumption, and cost. In our view, optimality can only be achieved through the emergence of embedded systems as a discipline in its own right.
Hard Real-Time Development Environments -- Executive Overview on Hard Real-Time Development Environments -- Hard Real-Time System Development -- Current Design Practice and Needs in Selected Industrial Sectors -- Tools for Requirements Capture and Exploration -- Tools for Architecture Design and Capture -- Tools for Programming, Code Generation, and Design -- Tools for Verification and Validation -- Middleware for Implementing Hard Real-Time Systems -- Review of Some Advanced Methodologies -- Component-Based Design and Integration Platforms -- Executive Overview on Component-Based Design and Integration Platforms -- Component-Based System Development -- Current Design Practice and Needs in Selected Industrial Sectors -- Components and Contracts -- Component Models and Integration Platforms: Landscape -- Standardization Efforts -- References -- Adaptive Real-Time Systems for Quality of Service Management -- Executive Overview on Adaptive Real-Time Systems for Quality of Service Management -- Adaptive Real-Time System Development -- Current Design Practice and Needs in Selected Industrial Sectors -- Real-Time Scheduling -- Real-Time Operating Systems -- QoS Management -- Real-Time Middleware -- Networks -- Programming Languages for Real-Time Systems -- Other Issues -- Execution Platforms -- Executive Overview on Execution Platforms -- Current Design Practice and Needs in Selected Sectors -- Computing Platforms -- Low Power Engineering.
Keywords: Computer science; Computer communication systems; Special purpose computers; Software engineering; Programming languages (Electronic computers).; Operating systems (Computers).; Management information systems; Computer Science; Special Purpose and Application-Based Systems; Software Engineering; Programming Languages, Compilers, Interpreters; Computer Communication Networks; Operating Systems; Management of Computing and Information Systems; Electronic books